(untitled) (Theatrum historiae, 2011)
The paper deals with the political and artistic career of Portuguese intellectual and journalist António Ferro. He belonged to those members of the European intellectual elite who envisioned a “new order” and its construction both in Portugal and Europe. Inspired by new artistic movements and the political experience of Sidónio Pais, Gabrielle D’Annun- zio, and Benito Mussolini, Ferro had to revise his ideas under Salazar’s Estado Novo (New State), regime inspired by national and European counter-revolutionary ideas and papal encyclicals. In that way, Ferro found himself between two strong political, ideological and cultural trends. The paper examines Ferro’s initial political ideas and his subsequent career as a leader of Salazar’s propaganda machine – SPN.